Inhibition of KCTD10 Affects Diabetic Retinopathy Progression by Reducing VEGF and Affecting Angiogenesis - Yun Feng; Cong Wang; Guangwei Wang (Genetics Research)
Aim. We purposed to evaluate the KCTD10 effects of angiogenesis in diabetic retinopathy (DR). Methods. We induced a DR cell model using high glucose (HG) treatment of HRECs and ARPE-19 cells. A DR rat was established by injecting streptozotocin. Small interference RNA targeted KCTD10 (si-KCTD10) was used to mediate KCTD10 inhibition in cell and animal models. The roles of KCTD10 on cell viability, apoptosis, angiogenesis, and related proteins (VEGF and HIF-1α) were observed by RT-qPCR, Western blot, CCK-8 assay, TUNEL staining, tube formation assay, ELISA, and immunohistochemistry assay. Results. KCTD10 expression was upregulated in DR cells and retinal tissue of DR rats. Treatment of the cells with si-KCTD10 increased cell viability and decreased apoptosis and angiogenesis in DR cells. Inhibition of KCTD10 could reduce the expression of VEGF and HIF-1α in DR cells. Furthermore, KCTD10 inhibition reduced VEGF levels in the retinal tissue of DR rats. Conclusion. This work showed that inhibition of KCTD10 relieved angiogenesis in DR.